Biomarcadores de poluição em camarões Macrobrachium amazonicum (Decapoda: Palaemonidae) oriundos de região Amazônica com histórico de contaminação por arsênio - FERREIRA, Johnata Azevedo (2018)
Manganese exploration in Serra do Navio (AP), its transport to Santana City (AP) and the processing of ore in the region were factors that led to the release of a large amounts of arsenic (As) on adjacent water system. This study aims to evaluate biochemical biomarkers: glutathione-S-transferase activity (GST), total antioxidant capacity against peroxyl radical (ACAP) and lipoperoxidation content (LPO) in residents animals from sites with arsenic contamination history, using the shrimp Macrobrachium amazonicum as biomonitor organism. In this study, the organisms were captured in August/2013 (Dry season , ET) and March/ 2014 ( rainy season , CH ) in three points with distinct arsenic histories of contamination : the mouth of the Amazon River , the Elesbão community - AP ( place with history the contamination) , Beija-Flor river, Mazagão- AP (tributary of the Amazon river , located 16 km from the site historically contaminated) and the Campumpema river , Abaetetuba - PA (tributary of the Para river , site without contamination history and located about 100 km from the first site). The animals were sampled using matapis and immediately anesthetized on ice. Then, the gills and muscle were dissected and separated for biochemical analysis. Also water samples were collected for analysis of arsenite content (AsIII) and arsenate (AsV ) at all sampling sites . In the analysis of the water was only found the presence of AsV, with higher concentrations in water from CH compared to ET. It is noted a AsV gradient of concentration in the water, where there is an increase of AsV from reference environment (Campumpema river) towards contaminated environments (Beija-Flor and Amazon rivers). About the biomarkers, the most significant results were found in the gills of shrimp. In this tissue, the total antioxidant capacity (ACAP) showed no significant differences between the sites sampled in the dry season. However, during the rainy season, this biomarker was higher in animals of the most contaminated environments compared to the dry season. The GST activity in the dry season was lower in animals of environments with higher As content in water. In the rainy season the activity of this detoxification enzyme was induced only in animals collected in the nearest environment to Mn beneficiation site.The lipid peroxidation during both dry and rainy seasons was lower in Beija-Flor river’s animals, with an increase of this oxidative damage in animal from Campumpema and Amazon rivers from dry season to the rainy season . It can be concluded that during the rainy season when there is an increase of AsV concentration in the water, the organisms from contaminated environments can induce antioxidants responses. The Beija-Flor river’s shrimps showed higher detoxifying capacity in relation to other points, representing the lowest levels of LPO, both in the rainy season and the dry season, probably in response to a more prolonged exposure to contaminants due to lower hydrodynamic of this water body.